The Next Generation of Collective Action Research - Wright, Stephen C. (Journal of social issues, 2009)
The articles presented in this volume describe part of a new generation of interest and vigor in the social psychological study of collective action. This new wave builds nicely on the foundation set by social identity, self‐categorization, and relative deprivation theories but also introduces a number of important innovative perspectives and variables. In this commentary, I review some of these expansions and additions, raise a number of conceptual concerns that arise out of these new directions, and discuss more generally some novel and important directions that emerge from the work presented in the volume and in other recent work on collective action.